Cell Sorting: Levitating Cells to Sort the Fit and the Fat (Adv. Biosys. 6/2020). Issue 6 (12th June 2020) - Puluca, Nazan; Durmus, Naside Gözde; Lee, Soah; Belbachir, Nadjet; Galdos, Francisco X.; Ogut, Mehmet Giray; Gupta, Rakhi; Hirano, Ken‐ichi; Krane, Markus; Lange, Rüdiger; Wu, Joseph C.; Wu, Sean M.; et al.
Abstract : In article number 1900300, Naside Gözde Durmus, Sean M. Wu, Utkan Demirci, and co‐workers show that magnetic levitation defines the fine balance of living cells where fatty and healthy populations of iPS‐derived cardiomyocytes levitate to a precise height under the magnetic field inside a microfluidic setup engineered as meticulously as the geometry of the pyramids.